Petrotectonics of Thoen Plutonic Rocks, Lampang Province, Eastern Granitic Belt of Thailand - Jundee, Patcharin Kosuwan; Phajuy, Burapha; Limtrakun, Phisit; Boonsoong, Apichet; Saraphanchotwitthaya, Panjai; Chandon, Ekkachak; Suatrong, Thanittha; Thapthanee, Pinpan (Trends in Sciences, 2025)
The plutonic rocks cropped in area of Thoen District, Lampang Province. The felsic to intermediate igneous rocks compositionally range from rhyolite, monzogranite to quartz monzonite, monzonite, granodiorite, diorite to gabbroic diorite with titanite as a minor constituent, characteristic of I-type granitic rocks. Based on minerals characters, 21 plutonic rock samples can be divided into 4 magmatic groups: Group I rhyolite, Group II monzogranite, Group III granodiorite and quartz monzonite, and Group IV granodiorite, diorite, monzonite and gabbroic diorite. Based on major and trace elements can be classified into 2 groups felsic to intermediate plutonic rocks and felsic volcanic rock (Group I, Group II and Group III) and intermediate mafic plutonic rocks (Group IV). The felsic intermediate plutonic rocks and felsic volcanic rock are the presence of mainly high-K calc-alkaline granite, I-type magma series that have active continental margins, with the involvement of continental crust. The intermediate to mafic plutonic rocks range from low-K to high-K calc-alkaline and shoshonitic series, indicating the feature of continental volcanic arc magma. All Thoen plutonic rocks have similar patterns in their chondrite and primitive mantle normalized patterns. Chondrite-normalized REE patterns are LREE enrichments and HREE depletion with negative Eu and Nb anomalies that are typical of volcanic arc granites. N-MORB normalized multi-element patterns are variable LILE enrichments (Rb, Ba, Th, Ce), HFSE depletions (Ta, Nb, Sr and Ti) and are typical of I-type volcanic arc granites. Thoen pluton is the part of EGB that indicates the magmatism along the boundary between Sukhothai Arc and Inthanon Zone. HIGHLIGHTS Thoen felsic to intermediate plutonic and felsic volcanic rocks are high-K calc-alkaline granite, with I-type magma series and intermediate to mafic plutonic rocks ranging from low K to high-K calc-alkaline and shoshonitic series. Chondrite-normalized REE patterns are enrichments in LREE and depletions in HREE. N-MORB normalized multi-element patterns are LILE enrichments and depletions in HFSE. The tectonic setting of Thoen plutonic is a volcanic arc in an active continental margin that is a part of the Eastern Granitic Belt. GRAPHICAL ABSTRACT